Digital Peripheries The Online Circulation of Audiovisual Content from the Small Market Perspective - Szczepanik, Petr; Zahrádka, Pavel; Macek, Jakub; Stepan, Paul (Springer Series in Media Industries, 2020)
This is an open access book. Media industry research and EU policymaking are predominantly tailored to large (and, in the latter case, Western) European markets. This open access book addresses the specific qualities of smaller media markets, highlighting their vulnerability to global digital competition and outlining survival strategies for them. New online distribution models and new trends in the consumption of audiovisual content are limited by, and pose new challenges for, existing audiovisual business models and their legal framework in the EU. The European Commission's Digital Single Market (DSM) strategy, which was intended e.g. to remove obstacles to the cross-border distribution of audiovisual content, has triggered a heated debate on the transformation of the existing ecosystem for European screen industries. While most current discussions focus on the United States, Western Europe, and the multinational giants, this book approaches these industry trends and policy questions from the perspective of relatively small and peripheral (in terms of their population, language, cross-border cultural flows, and financial and/or symbolic capital) media markets.